Basic Immunization Counseling for Babies in the New Village of Ladang Bambu, Medan Tuntungan District in 2019 - Helena Fransysca; Dwi Ris Hasanah (Science Midwifery, 2019)
The purpose of this study was to determine whether mothers understand the prevention of stunting in infants. And the activities carried out to increase maternal knowledge to obtain complete basic immunizations increase maternal knowledge about the side effects of each basic immunization vaccine. The type and form of activity of this activity is the provision of material to mothers regarding basic immunization, giving immunizations to infants. Results To achieve the objectives of the above activities, activities were carried out, including the delivery of material on basic immunization for infants.